Mothers’ Employment and Nutritional Status of Under-five Children Attending Selected Child Welfare Centre, Dhaka Cantonment (Journal of Armed Forces Medical College, Bangladesh, 2021)
Introduction: Nutritional status of children is one of the major predictors of child survivors and a proxy indicator for assessing the entire population health status. Despite the various efforts, malnutrition among children is remaining as a major public health problem in Bangladesh. Maternal employment status exerts strong influence over child nutrition status.Aim: To find out the effect of maternal employment on nutritional status of 0-59 month-old children attending Malabika CWC at Dhaka Cantonment.Methods: This cross sectional study was conducted at ‘Malabika’ Child Welfare Centre at Dhaka Cantonment from 01 March 2012 to 30 June 2012. A total of 110 children were selected conveniently. Data were collected from mothers by face to face interview and analyzed by SPSS 19. Association was assessed with Chi square test. The prevalence of malnutrition assessed by different indices of nutritional status based on Weight for Age Z-score, Height for Age Z-score and Weight for Height Z –Score following the WHO and NCHS guidelines and cut-off points.Results: The prevalence of stunting, underweight and wasting was found to be 61.4%, 56.3% and 61.3% among the children of employed mother respectively. These all 3 prevalence are higher than the children of unemployed mothers. The association between nutritional status of under-five children of employed and non-employed mothers was found statistically significant (p